PENGARUH DEFERRED TAX & TAX TO BOOK RATIO TERHADAP FIRM PERFORMANCE - Andre Sihombing; Francis Hutabarat (Klabat Accounting Review, 2023)
The purpose of this study was to determine the effect of deferred tax & tax-to-book ratio on company performance. Technological developments affect many business sectors, including the technology sector, but every company must understand the tax in their company. The population and research samples use companies on the IDX in the technology sector. There are 48 research samples from 4 years of observation 2018-2021. This study analyzes with regression analysis the research variables, namely deferred tax, tax to book ratio, company performance. The results of the study show that there is a significant influence between deferred taxes and company performance in the corporate technology sector on the Indonesia Stock Exchange. In contrast, company performance is not affected by the tax to book ratio in technology sector companies on the Indonesia Stock Exchange. Tujuan penelitian ini untuk mengetahui pengaruh deferred tax & tax to book ratio terhadap firm performance. Perkembangan teknologi mempengaruhi banyak sektor bisnis, termasuk sektor teknologi, namun setiap perusahaan harus memahami pajak dalam perusahaan mereka. Populasi dan sampel penelitian menggunakan perusahaan pada BEI di sector teknologi. Terdapat 48 sampel penelitian dari 4 tahun pengamatan 2018-2021. Penelitian ini menganalisa dengan analisa regresi variabel penelitian yaitu deferred tax, tax to book ratio, firm performance. Hasil penelitian menunjukkan ada pengaruh yang signifikan antara deferred tax dan firm performance pada perusahaan sektor teknologi di Bursa Efek Indonesia. Sebaliknya, firm performance tidak dipengaruhi tax to book ratio pada perusahaan sektor teknologi di Bursa Efek Indonesia. Kata Kunci: Deferred tax, tax to book ratio, firm performance